Epidemiological Study on the Status of Nutrition-Support Therapies by Emergency Physicians in China - Chi Niu; Wei Guo; Wei Gu (Emergency Medicine International)
Objectives. This study aimed to investigate the current status of nutrition-support therapies by emergency physicians in China and to provide an evidence-based case to improve the regulation of enteral and parenteral nutrition-support therapies. Methods. Physicians from the Emergency Branch of the China Geriatrics Society were enrolled in the present survey. A questionnaire related to nutrition-support therapy, including the time, location, ways, indications, complications, and nutrition-support training for physicians was answered. Results. 527 questionnaires were collected from over 300 hospitals in 25 provinces of China. The time to initiation of emergency nutrition support was often delayed. Furthermore, the treatment intensity and standardized training of physicians are weaknesses concerning nutrition support. Treatment standardization has been significantly improved, including blood glucose monitoring, precaution and management of complications, and the use of immunomodulators. Conclusions. Emergency physicians should pay attention to early identifying and providing nutrition support to those patients who need it. Finally, standardized training should be developed for emergency nutrition-support therapy.